5PSQ-071 Analysis of medication provided by patients. Issue 1 (23rd March 2023) - Soto, I; González, I; Mengual Barroso, MR; Rubio Cebrian, B; San Miguel Torvisco, P; Sollano-Sancho, I; Morona Minguez, I; Pousada Fonseca, A; Solis Olivares, J; Mateos Mateos, Y; Moriel Sanchez, C
Abstract : Background and Importance: Many patients bring medication with them during their admission to hospital, which is a source of error. Aim and Objectives: Analyse the prescription of medicines provided by the patient and evaluate their correct use. Material and Methods: Cross-sectional descriptive study of patients admitted to a second level hospital on 11-11-2021 which had treatments prescribed as 'medication provided by the patient' (MPP). The sources of information used were: the electronic medical record and the prescription programme. The variables collected were: age, sex, prescribing service, whether or not the medication was provided, patient knowledge of the dosage of the medication provided, number of total active ingredients prescribed per patient, and medications provided, number of therapeutic duplications in the complete treatment. Results: A total of 96 patients had a prescription for a MPP, representing 28.92% of the patients admitted to the hospital at that time. Of this total, after excluding those who could not be interviewed due to their clinical situation (Intensive Care, Resuscitation, Psychiatry, Emergency, Home Hospitalisation Unit and isolated patients), 42 patients were analysed, with a median age of 74.5 years [RIQ 70-80.75], 59.52% being male. The main prescribing service was internal medicine (59.52%) followed by surgery (16.67%) and traumatology (16.67%). Of the total number of patients with prescribed MPP, 85.71% actually provided it and 97.22% were aware of its dosage. The median number of active ingredients prescribed per patient was 13[RIQ 11-17], with the median number of MAPs being 2 [RIQ 1-2.75]. Therapeutic duplication was found between the medication provided and that of the admission in 2 patients. Conclusion and Relevance: A considerable percentage of patients admitted to the hospital provide medication, with the majority of patients belonging to the Internal Medicine Department. After the interview, it was observed that most of them controlled their medication; however, a significant percentage, despite having medication prescribed as provided, did not have it during their admission. For this reason, we consider that the patient should not provide medication as far as possible, in order to try to prevent medication errors during the hospital stay and to adjust his treatment to the hospital pharmacotherapeutic guide. References and/or Acknowledgements: Conflict of Interest: No conflict of interest